Rubber Nano Blends Preparation, Characterization and Applications - Markovic, Gordana; P. M., Visakh; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book summarizes the preparation, characterization and applications of rubber based nano blends. Rubbers from natural and synthetic polymers and their blends are discussed in the individual chapters, including nitrile, polyurethane, chlorosulphonated, polybutadiene, styrene butadiene, polychloroprene rubbers. In each chapter, contributors from academia and industry describe the preparation and characterization of the rubber blends. Therefore, a variety of characterization methods like tensile testing, differential scanning calorimetry, dynamical mechanical analysis, thermogravimetric analysis, electron microscopy, scattering and diffraction techniques, and rheology measurements are utilized. The authors evaluate the properties of the different materials and discuss numerous fields of application, ranging from biomedicine, packaging, coatings and automobile to aerospace.
Rubber Nano Blends -- Natural Rubber Nano Blends -- Nitrile Rubber Latex Blends -- Polyurethane Rubber-Based Nano Blends -- Chlorosulphonated Rubber-Based Nano Blends -- Polybutadiene Rubber-Based Nano Blends -- Styrene Butadiene Rubber-Based Nano Blends (SBR-nB) -- Polychloroprene Rubber-Based Nano Blends -- Ethylene Propylene Diene Rubber-Based Nano Blends.
Keywords: Polymers; Materials -- Analysis; Chemistry, Technical; Chemistry, Organic; Ceramic materials; Nanochemistry; Polymers; Characterization and Analytical Technique; Industrial Chemistry; Organic Chemistry; Ceramics; Nanochemistry